PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKUTURAL NUMBERED HEAD TOGETHER UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS X.6 SMA NEGERI 5 PEKANBARU - Sakdiah, Halimatun; ', Zulkarnain; ', Armis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was based on the students’ math achievement at class  X.6 SMAN 5 Pekanbaru the Mastery Minimum Criteria with percentage of 17,07%, there are only 7 students from 41 students who achieve the passing grade on the main discussion about relevancy with logica mathematic and then the learning process still teacher center. The research is class room action research. This research aims to increase learning process and students’ math achievement at clas X.6 SMAN 5 Pekanbaru through the implementation cooperative learning model of structural Numbered Heads Together. The subject of the research are  41 students from class X.6 SMAN 5 Pekanbaru consist of 18 male and 23 female students with the heterogenous level. The instruments of data collection in this research were observation sheets and students Mathematic tests. The research instrument consist of learning devices that involve Syllabus, Lesson Plan and Student Worksheet, and instrument data collector that involve the observation sheet and math achievement test. The observation sheets were analyzed in qualitative desciptive, while the students’ Mathematic tests were analyzed in quantitative descriptive. The qualitative descriptive showed an improvement of learning process prior to the action on the first and second cycle. The results of this research showed an increasing number of students’ math achievement from the basic score with the percentage 17.07% to 26.8% on the first daily test and 78.05% on the second daily test. Based on the result of this research can be concluded that the implementation of Cooperative Learning Model of structural approach Numbered Heads Together can improve students’ math achievement    at class X.6 SMAN 5 Pekanbaru in the second semester academic years 2015/2016.